miR-29a-5p Inhibits Prenatal Hair Placode Formation Through Targeting EDAR by ceRNA Regulatory Network - Jiang, Yao; Liu, Huatao; Zou, Quan; Li, Shujuan; Ding, Xiangdong (Frontiers in Cell and Developmental Biology, 2022)
Hair placode formation is an important stage of hair follicle morphogenesis and it is a complex process facilitated by non-coding RNAs. In this study, we conducted whole transcriptome sequencing analysis of skin, heart, liver, lung, and kidney tissues of day 41 (E41) normal and hairless pig embryos, and respectively detected 15, 8, and 515 skin-specific differentially expressed (DE) lncRNAs, miRNAs, and mRNAs. Furthermore, 18 competing endogenous RNA (ceRNA) networks were constructed. Following weighted gene co-expression network analysis (WGCNA) of stages E39, E41, E45, E52, and E60, between normal and hairless pig embryos, only two ceRNAs (lncRNA2162.1/miR-29a-5p/BMPR1b and lncRNA627.1/miR-29a-5p/EDAR) that showed period-specific differential expression in E41 skin were retained. Dual-luciferase reporter assays further indicated that EDAR was a direct, functioning target of miR-29a-5p and that no binding site was found in BMPR1b. Moreover, miR-29a-5p overexpression inhibited the mRNA and protein expression of EDAR while no significant differential expression of BMPR1b was detected. In addition, over-expressed lncRNA627.1 reduces the expression of miR-29a-5p and increase EDAR expression while inhibits lncRNA627.1 resulted in a opposite expression trend. Cell proliferation result demonstrated that lower expression of EDAR and lncRNA627.1 inhibited hair placode precursor cells (HPPCs) proliferation in a manner similar to that shown by over-expressed miR-29a-5p. This study identified that miR-29a-5p inhibited HPPCs proliferation via the suppression of EDAR expression in the EDA/EDAR signaling pathway, while lncRNA627.1 rescues EDAR expression. Our study provides a basis for a better understanding of the mechanisms underlying the ceRNA complex, miR29a-5p/EDAR/lncRNA627.1, that could regulate hair placode formation, which may help decipher diseases affecting human hair.